(Des)iguales y (des)conectados : políticas, actores y dilemas info-comunicacionales en América Latina (Colección Grupos de trabajo, 2021)
In this book we propose to work on one of the contemporary problems of the field, which was crudely exposed from the planetary catastrophe that the pandemic has meant "COVID 19: info-communicational inequality, which has connectivity and its reverse, disconnection, like some of its core points."